2016
DOI: 10.1155/2016/7486425
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel RD1 Antigens and Their Combinations for Diagnosis of Sputum Smear−/Culture+ TB Patients

Abstract: Rapid and accurate diagnosis of pulmonary tuberculosis (PTB) is an unresolved problem worldwide, especially for sputum smear− (S−) cases. In this study, five antigen genes including Rv3871, Rv3874, Rv3875, Rv3876, and Rv3879 were cloned from Mycobacterium tuberculosis (Mtb) RD1 and overexpressed to generate antigen fragments. These antigens and their combinations were investigated for PTB serodiagnosis. 298 serum samples were collected from active PTB patients, including 117 sputum smear+ (S+) and sputum cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“… 19 , 41 Proteins, such as Rv1985c, Rv3871, Rv3876 and Rv3879, that originated from RD 2 and 1 were demonstrated to be promising antigens in TB diagnostics, while Rv2659c was more suitable for diagnosis in latent TB patients. 23 , 27 , 30 In our study, the results of anti-Rv0310c-E, based on RD 8, and anti-Rv1255c-E, based on RD 10, IgG titers were significantly higher in TB patients than controls. Using ROC analysis, we found that anti-Rv0310c-E and anti-Rv1255c-E IgG antibodies exhibited similar AUC values.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“… 19 , 41 Proteins, such as Rv1985c, Rv3871, Rv3876 and Rv3879, that originated from RD 2 and 1 were demonstrated to be promising antigens in TB diagnostics, while Rv2659c was more suitable for diagnosis in latent TB patients. 23 , 27 , 30 In our study, the results of anti-Rv0310c-E, based on RD 8, and anti-Rv1255c-E, based on RD 10, IgG titers were significantly higher in TB patients than controls. Using ROC analysis, we found that anti-Rv0310c-E and anti-Rv1255c-E IgG antibodies exhibited similar AUC values.…”
Section: Discussionsupporting
confidence: 44%
“…The optimal operating point for each antigen at the maximum value of YI was calculated from the ROC analysis, and the corresponding sensitivity and specificity were determined. 30 The overall diagnostic performances of individual antigens for active TB are shown in Table 3 . The best performing antigen in the SPPT group was Rv0310c-E (YI: 0.5602), while it was Rv1255c-E (YI: 0.5674) in the SNPT group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Liu et al . combined Rv3871, Rv3876, and Rv3879 proteins and improved the diagnostic ability in PTB‐SN(Liu et al ., ). In our study, parallel tests by combining two and three antigens among Rv0222, Rv3403c and ESAT6/CFP10 were similarly investigated to improve the sensitivity of TB diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The coincidence rates of Rv0222, Rv3403c and ESAT6/CFP10 proteins in the diagnosis of PTB-SP, PTB-SN, and EPTB groups were not high, indicating that immune recognition of antigens varies in different patients, and that no definite antigen was identified in all or a majority of samples (Lyashchenko et al, 1998). Thus, Liu et al combined Rv3871,Rv3876, and Rv3879 proteins and improved the diagnostic ability in PTB-SN (Liu et al, 2016). In our study, parallel tests by combining two and three antigens among Rv0222, Rv3403c and ESAT6/ CFP10 were similarly investigated to improve the sensitivity of TB diagnosis.…”
Section: Discussionmentioning
confidence: 99%